Passively transferred myasthenia gravis: protection of mouse endplates by Fab fragments from human myasthenic IgG. Issue 9 (September 1980) - Toyka, K V; Löwenadler, B; Heininger, K; Besinger, U A; Birnberger, K L; Fateh-Moghadam, A; Heilbronn, E
Abstract : Using the mouse passive transfer model, the effects of purified human myasthenic immunoglobulin G and of the monovalent Fab fragment on neuromuscular junctions were investigated. Treatment with IgG markedly reduced amplitudes of miniature endplate potentials. When Fab fragments were transferred alone or with subsequent addition of IgG no neuromuscular transmission block was induced. Myasthentic IgG and Fab were specifically demonstrated at the neuromuscular junctions by immunohistochemistry. On electronmicroscopy endplate structure was normal in transfer experiments using IgG for up to 30 days. It is suggested that Fab fragments bind to acetylcholine receptors without affecting transmission and protect them from the attack of complete IgG antibodies.